Substrate stiffness and shear stress collectively regulate the inflammatory phenotype in cultured human brain microvascular endothelial cells - Alexis K. Yates; Heather Murray; Andrew Kjar; Daniel Chavarria; Haley Masters; Hyosung Kim; Alexander P. Ligocki; Angela L. Jefferson; Ethan S. Lippmann (Fluids and Barriers of the CNS)
Abstract Brain endothelial cells experience mechanical forces in the form of blood flow-mediated shear stress and underlying matrix stiffness, but intersectional contributions of these factors towards blood–brain barrier (BBB) impairment and neurovascular dysfunction have not been extensively studied. Here, we developed in vitro models to examine the sensitivity of primary human brain microvascular endothelial cells (BMECs) to substrate stiffness, with or without exposure to fluid shear stress. Using a combination of molecular profiling techniques, we show that BMECs exhibit an inflammatory signature at both the mRNA and protein level when cultured on gelatin substrates of intermediate stiffness (~ 30 kPa) versus soft substrates (~ 6 kPa). Exposure to modest fluid shear stress (1.7 dyne/cm2) partially attenuated this signature, including reductions in levels of soluble chemoattractants and surface ICAM-1. Overall, our results indicate that increased substrate stiffness promotes an inflammatory phenotype in BMECs that is dampened in the presence of fluid shear stress.